2021
DOI: 10.1007/s10291-021-01115-0
|View full text |Cite
|
Sign up to set email alerts
|

Clock bias prediction algorithm for navigation satellites based on a supervised learning long short-term memory neural network

Abstract: In a satellite navigation system, high-precision prediction of satellite clock bias directly determines the accuracy of navigation, positioning, and time synchronization and is the key to realizing autonomous navigation. To further improve satellite clock bias prediction accuracy, we establish a satellite clock bias prediction model by using long short-term memory (LSTM) that can accurately express the nonlinear characteristics of the navigation satellite clock bias. Outliers in the original clock bias should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…• Gross error removal and interpolation: Serious gross errors will affect the accuracy of clock error forecasting. The Median Absolute Deviation (MAD) can indicate gross errors in the data sequence (Huang et al, 2021a(Huang et al, , 2021b. After all gross errors are removed, the cubic spline interpolation method can be used to smooth fill in missing values.…”
Section: Data Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…• Gross error removal and interpolation: Serious gross errors will affect the accuracy of clock error forecasting. The Median Absolute Deviation (MAD) can indicate gross errors in the data sequence (Huang et al, 2021a(Huang et al, , 2021b. After all gross errors are removed, the cubic spline interpolation method can be used to smooth fill in missing values.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Since space-based atomic clocks are disturbed by factors such as mechanical vibration, electromagnetic radiation, and temperature changes, their clock error prediction models also include nonlinear random terms. Many studies have shown that neural network models have better forecasting effects on nonlinear data (Huang et al, 2021a(Huang et al, , 2021b. Among them, the Long Short-Term Memory (LSTM) neural network model exhibits a better forecasting effect on time series data (Greff et al, 2016;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…7). The ML models have been compared with several conventional non-ML models: regression model [14,80,101,159,160], brute force approach [143], traditional statistical approaches [60,94,[161][162][163][164], classical KF [129], Bayes-optimal rule [118], least square (LS)-based approach [40], Saastamoinen model [110], autoregressive model and a traditional LEO propagation model (EKF-STAN) [146], conventional wind speed retrieval method [43], Maximum-Likelihood Power-Distortion (PD-ML) [165], BERNESE 5.2 [114], CYGNSS [44], Hydrostaticseasonal-time (HST) model [49], Statistical Theta method [51][52][53]166], MAPGEO2004 geoid model [73], GNSS-IR soil moisture [58], Autoregressive (AR) and Autoregressive Moving Average (ARMA) [167], ERA-Interima global atmospheric reanalysis (now ERA5 reanalysis) [107], Empirical linear algorithms (LRM and LLM) [59], International Reference Ionosphere (IRI) 2016 model [168], NeQuick and IRI-2001 global TEC model [169][170][171], EKF-based integration scheme [172], CODE GIMs (Global Ionospheric Maps) [173], autoregressive integrated moving average (ARIMA), and quadratic polynomial (QP) models [174], least square regression algorithms (LSR) and bi-ha...…”
Section: E ML Vs Non-ml Models (Rq4a)mentioning
confidence: 99%
“…Their experimental results suggested that the accuracy and stability of the model were significantly better than those of traditional models such as the quadratic polynomial model and gray model; in particular, the advantage of this model was obvious when forecasting a cesium atomic clock. A further study [ 27 ] proposed a clock bias forecasting model that combined supervised learning and a long short-term memory neural network. The experimental results showed that the model had a significant advantage in controlling the accumulation of the forecasting error over time and that it was suitable for medium- and long-term clock bias forecasting.…”
Section: Introductionmentioning
confidence: 99%